Exploring the Impact of COVID-19 on the Healthcare System and Vulnerable Populations in the United States - Rachel Williams; Alagarsamy Srinivasan; Muthu Periasamy (University Library System, University of Pittsburgh, 2024)
Beginning in early 2020, SARS-CoV-2, the virus responsible for COVID-19, spread across the world, giving rise to a global pandemic that impacted billions of people. Surprisingly, the United States was among one of the worst affected countries with over a million deaths. The purpose of this review is to discuss the impact of COVID-19 in the United States from the perspectives of government policies and the U.S. healthcare system. The emergence of multiple viral variants was at the center of sequential waves of infection in the U.S., resulting in increased number of cases, hospitalizations, and deaths along with associated mental health sequelae in the population. Lack of uniform policies at the local, state, and federal levels exacerbated the situation. These factors contributed to significant healthcare worker burnout. Furthermore, the disease caused higher morbidity and mortality rates in specific groups such as lower average socioeconomic status, rural and underserved communities, Native Americans and African Americans, and older age groups (65+ years). The lessons learned from this broad analysis highlight many inadequacies and challenges experienced in the U.S. during the pandemic. Here we propose several suggestions for healthcare and government responses in the event of future unanticipated healthcare crises.